Predictors of Platelet Mitochondria Respiration in Children – The Arkansas Active Kids Study. (7th June 2021) - Diaz, Eva; Weber, Judith L; Cotter, Matthew; Porter, Craig; Adams, Sean H; Edwards, Timothy; Young, Catarina; Borsheim, Elisabet
Abstract: Objectives: Platelets play a critical role in the pathogenesis of atherosclerotic disease (AD). In the absence of a nucleus, platelet function and viability are largely dependent on the health of their mitochondria. The purpose of this study was to evaluate the association between common markers of cardiometabolic health in 7 to 10-year-old children and measures of platelet mitochondria function. Methods: Sixty children participated in a single study visit. Fasting blood was collected, and cardiorespiratory fitness (CRF, cycle ergometer test), physical activity (PA, accelerometers), and blood pressure percentiles were determined. Routine respiration (R) was measured by high-resolution respirometry (Oxygraph-2k) before platelets were permeabilized by digitonin. Thereafter, Complex I (CI) supported respiration was assayed in the leak (L), coupled (P) and uncoupled (CIE ) states. Complex IV (CIV) activity was assayed as a marker of respiratory capacity. Flux control ratios (FCR) were calculated by dividing respiratory fluxes by CIV. Multiple linear regression analyses were used to model FCRs (dependent variables) with age, sex, race, CRF, PA, Body Mass Index (BMI) percentile, HOMA2-IR, systolic (SBP-P)/diastolic blood pressure percentiles (DBP-P), triglyceride status, and Low Density Lipoprotein (LDL) status (status = high vs. normal) as dependent variables. Results: Age, race, LDL status and the interaction between BMI percentiles with SBP-P were retained in the final regression models for R, L, P and CIE FCRs. Specifically, R and CI supported respiration in the L, P and CIE states decreased with age ( P < .05), black race ( P < .05), and high LDL-cholesterol status ( P < .0001). To assess for the interaction between BMI and SBP-P, children were stratified as normal weight (NW) or overweight (OW = BMI ≥ 85 th percentile) with high (≥90 th percentile) or normal SBP. FCRs did not differ between NW groups. However, FCRs where ∼2 times higher in children with OW + high SBP compared to children with OW + normal SBP ( P < 0.05). Conclusions: Age, race, LDL cholesterol status, and systolic blood pressure are determinants of platelet bioenergetics in children. SBP-P modifies the association between weight status and platelet mitochondria respiration. Funding Sources: USDA-ARS 59-6250-4-001 and 6026-51, 000-012-06S. NIH-NIGMS 5P20GM10909, NIH 8UG1OD024945, NIH-NCATS 1UL1TR003107-0.